Mengurai Paradigma Pemidanaan Dalam Konteks Kebijakan Kriminal Di Era Digital (Law Research Review Quarterly, 2025)
The development of technology and information has created new spaces that offer convenience in life. However, behind this ease lies a loophole exploited by individuals with malicious intent. This space is used as a means to commit criminal acts. Crime in the digital era represents a modern type of offense that requires a different legal approach compared to conventional crimes. The shifting characteristics and modus operandi of criminal acts in the digital era must be met with a reconstruction of positive law in Indonesia. This is crucial to ensure that these crimes can still be effectively handled, thereby maintaining state order.